Alert: Michael Bennett #8 - Patterson, James, 1947-; Ledwidge, Michael; Mastrogiorgio, Danny; Leyva, Henry (New York, NY : Hachette Audio, 2015)
While pursuing terrorists responsible for two high-tech attacks and an assassination, detective Michael Bennett realizes that the attacks are a prelude to a bigger and more devastating event.
Title from container.
Read by Danny Mastrogiorgio and Henry Leyva.
Keywords: Bennett, Michael (Fictitious character) -- Fiction; New York (N.Y.) -- Fiction; Suspense fiction; Audiobooks